On the category of health in the novel «Ready Player One» by E. Cline; Лингвистические и культурологические аспекты современного инженерного образования - Пташкин А. С. Александр Сергеевич (2023, 2023)
This article considers the forms and means to express the category of health in the novel «Ready Player One» by E. Cline in English. The semantic space of the category of health includes the core, near periphery and the interpretative part. The interpretative semantic space was revealed as the distant periphery of the category under study. The data about the semantic structure of this mental unit was defined under the support of semantic and contextual analyses.